2016
DOI: 10.1080/14397595.2016.1259717
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of IL-6 blockade tocilizumab and TNF inhibitors on angiogenesis in synovial tissues from patients with rheumatoid arthritis

Abstract: These results demonstrated that inhibition of angiogenesis is a unique action of TCZ. Moreover, the data also suggest that lining layers proliferation might be closely associated with angiogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 25 publications
0
8
1
Order By: Relevance
“…In this regard, the observation of elevated levels of NGAL in RA patients after TCZ administration is contrary to the general anti-angiogenic effects mediated by TCZ. However, notably, NGAL plays many other pleiotropic roles unrelated to its role in angiogenesis, such as in protecting against bacterial infection by acting as an iron-carrying protein, in modulating oxidative stress, in promoting neutrophil chemotaxis, and in regulating thermogenesis and lipid metabolism by acting as an adipokine [10,30]. Moreover, although NGAL normally protects MMP-9 from degradation, we did not observe any elevation in MMP-9 serum levels in RA patients.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…In this regard, the observation of elevated levels of NGAL in RA patients after TCZ administration is contrary to the general anti-angiogenic effects mediated by TCZ. However, notably, NGAL plays many other pleiotropic roles unrelated to its role in angiogenesis, such as in protecting against bacterial infection by acting as an iron-carrying protein, in modulating oxidative stress, in promoting neutrophil chemotaxis, and in regulating thermogenesis and lipid metabolism by acting as an adipokine [10,30]. Moreover, although NGAL normally protects MMP-9 from degradation, we did not observe any elevation in MMP-9 serum levels in RA patients.…”
Section: Discussioncontrasting
confidence: 63%
“…Although it is known to lead to the accumulation of IL-6 in the serum of treated patients [2], TCZ reduces the production of pro-in ammatory cytokines, reduces CRP and SAA levels, and ameliorates the systemic manifestation of RA, such as pain, fatigue, and anemia [1,2,8]. While the effects of TCZ on angiogenesis have yet to be investigated in depth, TCZ has been shown to reduce VEGF serum levels in complete Freund's adjuvant (CFA)-induced arthritic rats [9], and to reduce the mean vessel density (MVD) in the synovium of RA patients as evaluated by immunohistochemical staining for the endothelial marker CD31 [10]. However, the detailed mechanisms of action, which enable TCZ to inhibit angiogenesis, are not yet understood.…”
Section: Introductionmentioning
confidence: 99%
“…TNF- α is released from macrophagocytes in the synovium and pannus and may have potent antioxidant and anti-inflammatory effects [ 33 ]. IL-6 can trigger the immune system by activating B-cells [ 34 ], releasing immunoglobulins, and increasing the production of rheumatoid factor [ 35 , 36 ]. It could also enhance the production of TNF- α and IL-1 β [ 15 ], thereby aggravating cartilage destruction [ 15 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that plenty abnormal signaling pathways are involved in the transformation of FLSs from friend to foe, such as excessive proliferation and subdued apoptosis of FLSs via P53 [ 8 , 9 ], P21 [ 10 12 ], Ras [ 13 ], Myc [ 14 ]. Further pathway examples include glucose-6-phosphate isomerase (G6PI) [ 15 ], HIF-1α [ 16 ] and TNFα [ 17 ], which mediate hypoxia-induced angiogenesis, contributed to pannus formation in RA synovia. Furthermore, plenty of activated signaling pathways promote the secretion of inflammatory factors and aggravated immune response [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%